(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Bronchiolitis is the most common reason for hospitalization among children younger than 2 years. Objective: The aim of the study was to assess the possibility that the associated risk factors in children suffering from bronchiolitis could predict the length of hospital stay and also to observe the immediate outcome. Methodology: This prospective study was conducted in a district hospital of Bangladesh in a period of two years from January 2011 to December 2012. Patients aged 2 years or less fulfilling inclusion criteria for bronchiolitis and required admission were enrolled in this study. Patients having comorbidities and who were discharged before fulfilling the study criteria for discharge were excluded from the study. Treatment was given according to National Guidelines for the Management of Bronchiolitis. All demographic, clinical and laboratory data were recorded in a prefixed questionnaire and analyzed. Results: Among 100 patients, 60% cases were hospitalized for 4 days or more. Mean duration of hospital stay was 4.37±1.93 days. Patients of male sex (67%), younger than 6 months of age (71%), preterm birth (21%), weight-for-age was either ≥2SD (60%) or ≤3SD (23%) were hospitalized for longer duration. Length of hospitalization was also increased in patients with family history of asthma (37%), smoking (75%), using wood-burning stoves for cooking (89%) and no previous history of respiratory distress (81%). Exclusively breastfed infants (41%) stayed hospital for shorter duration than those who fed partially (53%) or not at all (6%). All patients were improved in this case series (100%). Conclusion: Bronchiolitis patients having male sex, age less than 6 months, preterm born, partially breast fed , family history of asthma, exposure to smoking and wood-burning stoves were deduced to be significant risk factors for prolongation of length of hospitalization. Further research is needed to determine how these risk factors contribute to the development of the disease and prolong the length of hospital stay. Bangladesh Journal of Infectious Diseases 2020;7(2):67-71